An historical survey of the role of sport in society, with particular reference to Canada since 1700 - Howell, Maxwell Leo,1927- (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Ed. Ph.) -- University of Stellenbosch, 1969.